Impact of the competition between aggregation and surface growth on the morphology of soot particles formed in an ethylene laminar premixed flame. (February 2021) - Morán, José; Poux, Alexandre; Yon, Jérôme
Abstract: Soot particle surface growth may have a significant impact on aggregation kinetics, particle morphology, and both aggregate and monomer size distributions. Particularly, the morphological effects of surface growth are currently poorly understood. This is complex since surface growth also affects the kinetics of aggregation resulting in a time-dependent competition between both phenomena, producing very different morphological markers. The present study aims at improving our understanding of the morphological impact of surface growth by implementing this effect in a Monte Carlo discrete element code for the simulation of soot formation in an ethylene premixed flame. An asymptotic average primary particle overlapping ∼ 30 % is observed for different flame conditions. The primary particle coordination number is highly sensitive to surface growth rate and particle volume fraction, and maximum values are on average within the 4 - 8 range. The particle local compacity, as quantified by the packing factor, is also considerably increased when aggregates experience surface growth, contrarily to the fractal structure of individual aggregates that seems more dependent on the aggregation regime. Finally, surface growth narrows both the primary particle and aggregate size distributions. Graphical abstract: Highlights: A new semi-analytical expression for aggregate's volume and surface area is proposed. Predominance of surface growth over aggregation on cluster mass growth is quantified. Determination of overlapping coefficient and coordination number distributions. Surface growth reduces both monomer and aggregate's geometric standard deviation. Surface growth induces an increase of aggregate's local compacity.